EKSPLORASI TEKNIK PAYET PADA BUSANA PESTA KOSTUM DENGAN INSPIRASI PHANTOM GRACIOUS - Ahmad Saepunajah; Cucu Ruhidawati (Fesyen Perspektif, 2017)
Party costume dress is one type of the party dress which is often used in a party with a certain dress code or costumes. Party costume dresses usually made with full of artistic value obtained from its inspiration and interpreted into a unique form. An inspiration can be obtained from various things, one of them is Phantom Gracious. Phantom Gracious is a concept derived from a hybrid engineering with scientific and other field of technology, produce a mysterious look, unique, somewhat spooky yet beautiful and wonderful look. Phantom Gracious impressions can be expressed in various ways, can be by using some dark colors, some monstrous materials like modular textiles, or can be by using a simple material like sequin as a garniture. The author explores the sequin technique that are placed on different media from previous one, not directly attached to the cloth with the aid of thread, but rather affixed to the wire media. The wire formed in such a way as the twigs and then attached to the dress as a garniture. Using this exploration of sequin technique will add some unique, mysterious, elegant and glamour value, and the expectation of using this exploration is the result of product have an appropriate impression with the concept of Phantom Gracious and can be accepted among the fashion lover and costumes industry.